Decomposition of Practice as an Activity for Research-Practice Partnerships. (July 2019) - Resnick, Alison Fox; Kazemi, Elham
This analysis examines the process of one research-practice partnership (RPP) engaged in the activity of decomposing elementary principal practice in the context of an instructional improvement initiative in mathematics. Decomposing, or breaking apart, complex practice has been used primarily by researchers to inform the design of pre-service teacher education. We argue that decomposition is a rich activity for researchers and practitioners to collaboratively engage in to support improvement efforts where practitioners are expected to transform their day-to-day practice. We examine what can be learned from the process by which one RPP engaged in decomposing practice that might be useful for other RPPs. Our retrospective, qualitative analysis supports understanding of how RPPs might engage in decomposition and the role decomposition might play in supporting RPPs to foster educational transformation in local contexts.